Wiley 2012 interpretation and application of International Financial Reporting Standards - Mackenzie, Bruce; Coestee, Danie; Njikizana, Tapira; Chamboko, Raymond (John Wiley & Sons, 2012)
For many years, the International Accounting Standards Board (IASB) has been working to develop a set of accounting standards that can be used to bring about uniformity in financial reporting around the world.